The Effect of Digital Economy Networks on the Growth of Small and Medium Enterprises in West Java Case Study on E-commerce Platforms - Loso Judijanto; Eva Yuniarti Utami; Eko Sudarmanto; Nurlina Aris; Ahmadun Ahmadun (North Press, 2024)
This research investigates the impact of the digital economy network on the growth of Small and Medium Enterprises (SMEs) operating on e-commerce platforms in West Java. Utilizing a quantitative research design, data was collected from 110 SMEs through structured questionnaires, focusing on digital economy components such as Broadband Infrastructure, Digital Skills, Online Payment Systems, and Policy Support. The analysis, conducted using regression and correlation studies with SPSS 26, unveiled significant relationships between these components and SME growth indicators—Revenue Growth, Market Expansion, and Employment Generation. The results highlight the pivotal role of Broadband Infrastructure, emphasizing its positive influence on SME performance. The interconnectedness of digital economy components underscores the need for comprehensive strategies to foster a conducive ecosystem for SMEs in the evolving digital landscape. Policymakers, businesses, and stakeholders can leverage these insights to shape interventions and strategies that support the sustainable growth of SMEs in West Java's e-commerce sector.